2017
DOI: 10.1186/s12864-016-3381-z
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of starch metabolism genes in potato (Solanum tuberosum L.)

Abstract: BackgroundStarch is the principle constituent of potato tubers and is of considerable importance for food and non-food applications. Its metabolism has been subject of extensive research over the past decades. Despite its importance, a description of the complete inventory of genes involved in starch metabolism and their genome organization in potato plants is still missing. Moreover, mechanisms regulating the expression of starch genes in leaves and tubers remain elusive with regard to differences between tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
137
3
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(147 citation statements)
references
References 82 publications
1
137
3
6
Order By: Relevance
“…Previously, SuSy was identified as a major determinant of tuber sink strength and starch accumulation (Baroja‐Fernández et al, ; Zrenner et al, ). Our microarray data indicated a lower expression (but not more than twofold) of StSuSy4, the main isoform in tubers (Fu & Park, ; Van Harsselaar et al, ), under all stress conditions. Quantitative PCR with StSuSy4‐ specific primers confirmed that StSuSy4 expression clearly decreased in tubers grown under elevated temperatures (heat and heat plate) while cooling the root space attenuated the effect (Figure b).…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Previously, SuSy was identified as a major determinant of tuber sink strength and starch accumulation (Baroja‐Fernández et al, ; Zrenner et al, ). Our microarray data indicated a lower expression (but not more than twofold) of StSuSy4, the main isoform in tubers (Fu & Park, ; Van Harsselaar et al, ), under all stress conditions. Quantitative PCR with StSuSy4‐ specific primers confirmed that StSuSy4 expression clearly decreased in tubers grown under elevated temperatures (heat and heat plate) while cooling the root space attenuated the effect (Figure b).…”
Section: Resultsmentioning
confidence: 63%
“…Because the accumulation of transitory starch was clearly decreased in leaves grown under heat conditions (Figure c), expression profiles of starch genes as described by Van Harsselaar, Lorenz, Senning, Sonnewald, and Sonnewald () were analysed (Table S7). Expression of important starch biosynthetic genes, such as ADP‐glucose pyrophosphorylase large subunits 1 and 3 ( StAPL1 , StAPL3 ), granule‐bound starch synthase 1 ( StGBSS1 ), or starch branching enzyme 3 ( StSBE3 ), was clearly reduced under heat and cold plate conditions suggesting that starch biosynthesis was hampered by elevated temperatures (Figure d).…”
Section: Resultsmentioning
confidence: 99%
“…As of March, 2017, the original publication of the DM sequence has been cited more than 500 times, providing a framework for studies of gene families (Charfeddine et al 2015;Gao et al 2016;Ma et al 2016;Schreiber et al 2014;Seo et al 2016;Tang et al 2016;Van Harsselaar et al 2017), a scaffold for alignment of transcriptomic data (Campbell et al 2014;Gong et al 2015;Goyer et al 2015;Liu et al 2015;Morris et al 2014;Tang et al 2014) or a reference genome against which to discover genomic variation (Hardigan et al 2016), to cite just a few. As sequencing platforms improve, the DM assembly will likely be supplanted by that of a more robust commercial potato line.…”
Section: Resultsmentioning
confidence: 99%
“…Ветвление амилопектина осуществляет ветвящий фермент SBE (starch-branching enzyme, EC 2.4.1.18), который отщепляет от неразветвлен-ной цепочки фрагмент и переносит его к шестому атому углерода глюкозы (Zhang et al, 2017). Путь биосинтеза крахмала описан во многих источниках, в то время как регуляция этого процесса до сих пор остается малоизу-ченной (Van Harsselaar et al, 2017).…”
Section: ассоциативная семантическая сеть молекулярно-генетической реunclassified
“…Так, например, на сети по-казана активация аденозиндифосфат-глюкоза-пирофос-форилазы белком NADP-зависимой тиоредоксинредукта-зой C (NTR3), которая приводит к накоплению крахмала (Jenner et al, 2001;Michalska et al, 2009;Geigenberger, 2011). Известно, что экспрессия генов LOB, TIFY5a и WRKY4 положительно коррелирует с экспрессией генов SuSy4 и GPT2.1 (Van Harsselaar et al, 2017). На рис.…”
Section: ассоциативная семантическая сеть молекулярно-генетической реunclassified